PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DAN MOTIVASI KERJA GURU TERHADAP KINERJA GURU SEKOLAH DASAR NEGERI DI KECAMATAN BENGKALIS KABUPATEN BENGKALIS - ROLAS WAHYUDI; M. NUR MUSTAFA; SUMARNO SUMARNO (Jurnal JUMPED (Jurnal Manajemen Pendidikan), 2017)
This study aims to investigate the influence of variables (1) the principal’sleadership on teacher performance, (2) work motivation of teachers on teacher performance,(3) the principal’s leadership and motivation of teachers working together on teacherperformance. Respondents are state elementary school teacher in District Bengkalis totaling87 people were obtained by simple random sampling technique. Data collected throughquestionnaire as a research instrument. Analysis of the data used is descriptive analysis, inferentialstatistical analysis and hypothesis testing. Instrument reliability coefficient is calculated usingCronbach alpha. In partial results showed the positive influence among the leadership of theprincipal on teacher performance of 0.332, and a positive influence between work motivationof teachers on teacher performance of 0.354. While simultaneously the influence of schoolleadership and motivation of teachers on teacher performance of 0.418.